2018
DOI: 10.1364/boe.9.002336
|View full text |Cite
|
Sign up to set email alerts
|

Effective bidirectional scanning pattern for optical coherence tomography angiography

Abstract: Abstract:We demonstrate the utility of a novel scanning method for optical coherence tomography angiography (OCTA). Although raster scanning is commonly used for OCTA imaging, a bidirectional approach would lessen the distortion caused by galvanometer-based scanners as sources continue to increase sweep rates. As shown, a unidirectional raster scan approach has a lower effective scanning time than bidirectional approaches; however, a strictly bidirectional approach causes contrast variation along the B-scan di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 33 publications
(16 reference statements)
0
18
0
Order By: Relevance
“…2) 3D OCTA mode: 400 A-line per B-scan, 4 repeated B-scans per imaging plane, 400 planes, and total image number: 1600. Bi-directional B-scan protocol is utilized in order to eliminating time required for galvo fly-back [31], thus optimizing imaging throughput. Image acquisition time is only 3.2 seconds, with B-scan interval of 2.5 ms. 3) 3D structural OCT mode: similar scan protocol to OCTA, but without repeated scanned at each B-scan position.…”
Section: Scanning Protocolmentioning
confidence: 99%
“…2) 3D OCTA mode: 400 A-line per B-scan, 4 repeated B-scans per imaging plane, 400 planes, and total image number: 1600. Bi-directional B-scan protocol is utilized in order to eliminating time required for galvo fly-back [31], thus optimizing imaging throughput. Image acquisition time is only 3.2 seconds, with B-scan interval of 2.5 ms. 3) 3D structural OCT mode: similar scan protocol to OCTA, but without repeated scanned at each B-scan position.…”
Section: Scanning Protocolmentioning
confidence: 99%
“…A bidirectional scanning protocol (Fig. 2) using a triangular function on the fast-axis has been developed recently on a 200-kHz SS-OCT system [20]. The forward scanning and the backward scanning are consecutively acquired without the use of fly-back scans.…”
Section: Bidirectional Scanning Protocols Opts Out Of Fly-back Timementioning
confidence: 99%
“…Many previous research works have demonstrated different scanning methods to decrease noise [19], increase efficiency [20,21] or increase the velocity ranging in OCT applications [22,23]. Recently, a pilot version of HDR-OCTA, variable inter-scan time analysis (VISTA), demonstrated sufficient sensitivity to detect flow impairment before the onset of capillary dropout [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, to minimize the impact of motion artifact in handheld QME, we demonstrate a custom bidirectional scan pattern, capable of scanning a 6 × 6 × 1 mm volume of tissue in 3.4 seconds. Recently, a bidirectional triangular scan pattern using galvanometer-based scanners has been developed in OCT angiography [27]. In our method, we use the MEMS mirror with a similar bidirectional scan pattern which comprises two regions: a linear scan region where B-scans are acquired, and a sinusoidal turn-around region where the scanning direction of the beam is reversed whilst avoiding the resonant behavior of the MEMS mirror.…”
Section: Introductionmentioning
confidence: 99%